Empirical profiling of cold hydrogen plumes formed from venting of LH2 storage vessels. (16th September 2021) - Buttner, W.J.; Ciotti, M.; Hartmann, K.; Schmidt, K.; Wright, H.; Weidner, E.
Abstract: Liquid hydrogen (LH2 ) storage is viewed as a viable approach to assure sufficient hydrogen capacity at commercial fuelling stations. Presently, LH2 is produced at remote facilities and then transported to the end-use site by road vehicles (i.e., LH2 tanker trucks). Venting of hydrogen to depressurize the transport storage tank is a routine part of the LH2 delivery and site transfer process. The behavior of cold hydrogen plumes has not been well characterized because of the sparsity of empirical field data, which can lead to overly conservative safety requirements. Committee members of the National Fire Protection Association (NFPA) Standard 2 [1] formed the Hydrogen Storage Safety Task Group, which consists of hydrogen producers, safety experts, and computational fluid dynamics modellers, has identified the lack of understanding of hydrogen dispersion during LH2 venting of storage vessels as a critical gap for establishing safety distances at LH2 facilities, especially commercial hydrogen fuelling stations. To address this need, the National Renewable Energy Laboratory Sensor Laboratory, in collaboration with the NFPA Hydrogen Storage Task Group, developed a prototype Cold Hydrogen Plume Analyzer to empirically characterize the hydrogen plume formed during LH2 storage tank venting. The prototype analyzer was field deployed during an actual LH2 venting process. Critical findings included: Hydrogen above the lower flammable limit (LFL) was detected as much as 2 m lower than the release point, which is not predicted by existing models. Personal monitors detected hydrogen at ground level, although at levels below the LFL. A small but inconsistent correlation was found between oxygen depletion and the hydrogen concentration. A negligible to non-existent correlation was found between in-situ temperature measurements and the hydrogen concentration. The prototype analyzer is being upgraded for enhanced metrological capabilities, including improved real-time spatial and temporal profiling of hydrogen plumes and tracking of prevailing weather conditions. Additional deployments are planned to monitor plume behavior under different wind, humidity, and temperature conditions. The data will be shared with the Hydrogen Storage Task Group and ultimately will be used support theoretical models and code requirements prescribed in NFPA 2. Highlights: A prototype analyzer was used to measure cold hydrogen plume dispersion. Hydrogen above the LFL was observed below the horizontal point of release. Hydrogen buoyancy did not totally dominate the cold plume dispersion. The deployed analyzer can form the basis for a Hydrogen Wide Area Monitor (HyWAM).